Pengaruh Pasar Modal Syariah terhadap Pertumbuhan Ekonomi Indonesia - Khuluqi, Muhammad Ibrahim; Subchanifa, Dian Pujiatma Vera (Institut Agama Islam Negeri Kudus, 2026)
AbstractThis research is motivated by the continued growth of the Islamic capital market in Indonesia, but its contribution to national economic growth still requires empirical evidence. The development of Islamic stocks, sukuk, and Islamic mutual funds shows a positive trend, even though the Indonesian financial market experienced pressure due to the Covid-19 pandemic and global economic volatility. This study aims to analyze the influence of Islamic stocks, Islamic mutual funds, and sukuk on Indonesian economic growth. This study uses a quantitative approach with an associative research type. This study employs quarterly secondary data covering the period 2011–2025 obtained from the Financial Services Authority and the Central Bureau of Statistics. This study uses a multiple linear regression analysis method with the assistance of the EViews 9 application. The results show that Islamic stocks do not significantly influence Indonesian economic growth. Islamic mutual funds and sukuk have a positive and significant effect on Indonesian economic growth. This study shows that Islamic capital market instruments, particularly sukuk and Islamic mutual funds, have contributed to driving national economic growth through financing the productive sector.Keywords: Sharia Shares; Sharia Mutual Funds; Sukuk; Sharia Capital Market; Economic Growth.AbstrakPenelitian ini dilatarbelakangi oleh perkembangan pasar modal syariah di Indonesia yang terus meningkat, namun kontribusinya terhadap pertumbuhan ekonomi nasional masih memerlukan pembuktian empiris. Perkembangan saham syariah, sukuk, dan reksa dana syariah menunjukkan tren yang positif, meskipun pasar keuangan Indonesia sempat mengalami tekanan akibat pandemi Covid-19 dan volatilitas ekonomi global. Penelitian ini bertujuan untuk menganalisis pengaruh saham syariah, reksa dana syariah, dan sukuk terhadap pertumbuhan ekonomi Indonesia. Penelitian ini menggunakan pendekatan kuantitatif dengan jenis penelitian asosiatif. Data penelitian menggunakan data sekunder triwulanan periode 2011–2025 yang diperoleh dari Otoritas Jasa Keuangan dan Badan Pusat Statistik. Penelitian ini menggunakan metode analisis regresi linier berganda dengan bantuan aplikasi EViews 9. Hasil penelitian menunjukkan bahwa saham syariah tidak berpengaruh signifikan terhadap pertumbuhan ekonomi Indonesia. Reksa dana syariah dan sukuk berpengaruh positif dan signifikan terhadap pertumbuhan ekonomi Indonesia. Penelitian ini menunjukkan bahwa instrumen pasar modal syariah, khususnya sukuk dan reksa dana syariah, memiliki kontribusi dalam mendorong pertumbuhan ekonomi nasional melalui pembiayaan sektor produktif.Kata Kunci: Saham Syariah; Reksa Dana Syariah; Sukuk; Pasar Modal Syariah; Pertumbuhan Ekonomi.